PROMOTION AND PROSPECTS OF GREEN ECONOMY IN CENTRAL ASIA - Gaybullayeva G. M. (Galaxy International Interdisciplinary Research Journal, 2022)
The article discusses the comprehensive measures implemented in Uzbekistan in the field of green ecology development, aimed at deepening structural transformations, modernization and diversification of the basic sectors of the economy, and balanced socio-economic development of the territories. Research has shown that there are interrelated challenges and needs in ensuring an efficient, resource-efficient and environmentally sound economy in the face of climate change.